Analysis of Business Cycles in the Breeding of Pigs, Cattle and Poultry and their Relationship to the Causality of Wheat and Rye Cultivation in Poland - Mierzejewski, Mateusz; Lampart, Magdalena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2018)
The article presents a study on the phenomenon of pig gaps in the perspective of pig, cattle, and poultry farming in Poland. The work attempts to define the phenomenon itself as well as to show the reasons for its occurrence and significance for the Polish economy. The study used a cross-spectral analysis, which indicated cyclical relationships and shifts between the studied time series. The methodology of the work was based on a simplified spectral analysis, i.e. the use of the square of coherence, spectral density and phase spectrum. In addition, the article uses a comparative method for selected production volumes. The results were analyzed in the context of occurrence of pig cycles for breeding and cultivation. The study showed the occurrence of the relationship between pig breeding and wheat and rye cultivation.